Ultrastructure and intercellular contact-mediated communication in cultured human early stage follicles exposed to mTORC1 inhibitor. (7th October 2019) - Grosbois, J; Vermeersch, M; Devos, M; Clarke, H J; Demeestere, I
Abstract: The reproductive lifespan of a woman is determined by the gradual recruitment of quiescent follicles into the growing pool. In humans, ovarian tissue removal from its in vivo environment induces spontaneous activation of resting follicles. Similarly, pharmacological activation of the PI3K/Akt pathway leads to accelerated follicle recruitment, but has been associated with follicular damage. Recent findings demonstrate that everolimus (EVE), an mTORC1 inhibitor, limits primordial follicle activation. However, its potential benefit regarding growing follicle integrity remains unexplored. Ovarian cortical fragments were exposed to ± EVE for 24 h and cultured for an additional 5 days. After 0, 1 and 6 days of culture, fragments were either processed for ultrastructural analysis or subjected to follicular isolation for gene expression and immunofluorescence assessments. Data from transmission electron microscopy showed that growing follicles displayed similar ultrastructural features irrespective of the conditions and maintained close contacts between germinal and stromal compartments. Establishment of intra-follicular communication was confirmed by detection of a gap junction component, Cx43, in both groups throughout culture, whereas transzonal projections, which physically link granulosa cells to oocyte, formed later in EVE-treated follicles. Importantly, levels of GJA1 mRNA, encoding for the Cx43 protein, significantly increased from Day 0 to Day 1 in the EVE group, but not in the control group. Given that EVE-treated follicles were smaller than controls, these findings suggest that EVE might facilitate the establishment of appropriate intercellular communications without impairing follicle ultrastructure. Therefore, mTORC1 inhibitors might represent an attractive tool to delay the culture-induced primordial follicle activation while maintaining follicles in a functionally integrated state.